Kebebasan Berdagang Di Tengah PPKM Darurat Ditinjau Dari Sudut Pandang Sosiological Jurisprudence Dan Konsep Keadilan - Sukendar, Sukendar; Santoso, Aris Prio Agus; Rifai, Raden Ade; Hermawan, Risma Dewi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The government has implemented a Policy for the Imposition of Restrictions on Emergency Community Activities that have an impact on the trade sector, one of which is micro, small and medium enterprises. These business actors, in addition to experiencing a decrease in turnover, also received criminal sanctions in the midst of the imposition of this emergency Community Activity Restriction by the local government. The formulation of the problem in this study is how freedom of trade in the midst of the Imposition of Restrictions on Emergency Community Activities is viewed from the point of view of sociological jurisprudence and justice. The approach method used in this study is a normative juridical approach, with secondary data collection. Data collection in this research is by literature study. The results obtained were analyzed qualitatively. From the results of the study, it shows that in sociological jurisprudence, trading in the midst of the Imposition of Restrictions on Emergency Community Activities is a community right that becomes a public reality that should still be monitored and controlled without imposing fines even though the Salus Populi Suprema Lex Esto principle is the basis for implementing these sanctions. However, at least the legal ideals must still be considered in order to change social values in the community. In the concept of justice, trading in the midst of the Imposition of Restrictions on Emergency Community Activities is the right of everyone to defend their life and life which has been formulated by law in the form of rights and obligations. This emphasizes that the Government must still pay attention to justice by considering economic and social factors, which of course must be relevant to public order where a scale of justice is recognized.